PENINGKATAN KETERAMPILAN MEMBACA PUISI MENGGUNAKAN METODE DEMONSTRASI DI KELAS III SEKOLAH DASAR - Asna, Martaria; Halidjah, Siti; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research uses descriptive method that aims to describe the improvement of learning skills of Indonesian language in applying the demonstration method of students thirth years elementary school 21 Monterado Bengkayang Regency. The procedure in this research has 4 stages namely, planning, implementation, observation, and reflection. It is continuously done repeatedly until the research objectives are achieved, in this study has three cycles with each cycle conducted two meeting. This research technique uses observation technique and research instrument using observation sheet which is used to assess teacher ability that is based on instrumen I, instrumen II and student poetry reading skills. Based on the results of research conducted obtained instrumen I cycle I with an average of 2.93, cycle II with mean of 2.93 and cycle III with average 2.93. instrumen II obtained the results of cycle I with a mean of 2.21, cycle II with a mean of 3.18 and cycle III 3.63. While students' reading skilsl resulted in cycle I with average 25.31, cycle II with mean of 55.45 and cycle III 70.51. Based on these results, the demonstration method can provide improved poetry readi skills of students.Â Keywords: Reading Skills, Poetry, Demonstration MethodÂ